Values in China's Economic Diplomation - Arshid Muhammad (International Journal of Science and Society, 2020)
Rapid economic developments over the recent decades has made China to be the center of many researches. China has been known of having a unique technique of diplomacy. How a group of people interact with each other is strongly influenced by the values that has been developed in the social order. This paper uses research methods that focuses on literature reviews of books and articles that will explore the kind of values developed and is considered important and influential in the local society of China. This paper will also suggest techniques directly to China's economic diplomacy undertaken by both countries, individuals, or through joint venture